Business Performance Model of Micro, Small and Medium Enterprises (MSMEs) in Reducing Poverty Rates - Ayuni, Tyus Windi; Bhastary, Manda Dwipayani; Sari, Devi Purnama; Amelia, Ratih; Nasib, Nasib (International Journal on Social Science, Economics and Art, 2025)
Business performance of Micro, Small, and Medium Enterprises (MSMEs) is crucial in reducing poverty rates in a region. This is because business performance is believed to create jobs, increase community income, and drive local economic growth. There are three factors that influence the business performance of MSMEs: product innovation, digitalization or technology utilization, and marketing strategies. The urgency of this research stems from the absence of a business performance model for MSMEs aimed at reducing poverty rates in Langkat Regency. The objectives of this study are to identify the potential and challenges of MSMEs, formulate development strategies for MSMEs, and develop a business performance model based on innovation, digitalization, and marketing strategies to reduce poverty rates. The method used in this study is quantitative with Structural Equation Modeling (SEM) analysis. The results of the analysis are expected to contribute to the development of an effective business performance model for MSMEs in reducing poverty. From the study results, it was found that adjustments are needed to the model design developed in the previous study. Based on primary questionnaire data from 50 MSMEs in Langkat Regency, it was found that the factors influencing MSME business performance in Langkat Regency contribute to reducing poverty rates.